ANALISIS MEDIA PEMBELAJARAN MITIGASI BENCANA BERBASIS ADOBE FLASH DI SEKOLAH DASAR NEGERI 192 PEKANBARU - Lisa Safitri; Muhammad Jaya Adi Putra; Guslinda Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the process of developing adobe flash-based disaster mitigation learning media at 192 Pekanbaru Elementary Schools. This research was conducted at 192 Pekanbaru Elementary School in September 2019 - January 2020. This type of research is a research development, using the ADDIE model which consists of analysis, design. Development (implementation), implementation (implementation) and evaluation (evaluation). In collecting data in this study using one-on-one trials and limited trials. Based on the results of the research that has been done, it can be concluded that the learning media for adobe flash-based disaster mitigation after one-on-one tests has an average score of 84.41% with a very good category, then in a limited trial it is obtained an average score of 93.36 % with very good categories. Overall the level of user response to adobe flash-based disaster mitigation learning media is in the very good category.Key Words: Adobe Flash, Disaster Mitigation